Strengthening the Capacity of Nasyiatul Aisyiyah Branch Members through Digital Literacy and Social Leadership Programs - Siti Fatimah; Rini Kuswati; Retno Sintawati; Ahmad Baihaqi Esaputra; Zana Zein Hardimanto (Universitas Muhammadiyah Surakarta, 2026)
This community service program was conducted at the Branch Leadership of Nasyiatul Aisyiyah (PCNA) Colomadu, Karanganyar. One of the main challenges faced by PCNA is the absence of activities that encourage adolescents to participate in organizational activities and utilize their youth through positive and productive engagements. Therefore, this program was highly expected by the partner institution to facilitate the establishment of the Nasyiatul Aisyiyah Sub-Branch Leadership (PRNA) structure in Colomadu. The target community required support in terms of infrastructure and human resources to develop an organization capable of providing benefits to society. The objectives of this community service program were: (1) to establish the PRNA organizational structure; (2) to conduct leadership and digital literacy training; (3) to assist participants in improving their time management skills; and (4) to provide motivation regarding ethical values as Muslim female adolescents. The methods employed in this program included Focus Group Discussions (FGDs), training sessions, and mentoring activities. The outputs of this program consisted of video intellectual property rights (IPR), journal publications, community service reports, media coverage, and documentation uploaded to online media platforms and YouTube. Keywords: Organizational Structuring, Leadership, Time Management, Digital Literacy